2009
DOI: 10.1111/j.1471-4159.2009.06048.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β enhances nucleotide‐induced and α‐secretase‐dependent amyloid precursor protein processing in rat primary cortical neurons via up‐regulation of the P2Y2 receptor

Abstract: The heterologous expression and activation of the human P2Y2 nucleotide receptor (P2Y2R) in human 1321N1 astrocytoma cells stimulates α‐secretase‐dependent cleavage of the amyloid precursor protein (APP), causing extracellular release of the non‐amyloidogenic protein secreted amyloid precursor protein (sAPPα). To determine whether a similar response occurs in a neuronal cell, we analyzed whether P2Y2R‐mediated production of sAPPα occurs in rat primary cortical neurons (rPCNs). In rPCNs, P2Y2R mRNA and receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
104
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(111 citation statements)
references
References 77 publications
(153 reference statements)
6
104
0
1
Order By: Relevance
“…Similarly, UTP induced sAPPα shedding via ADAM10 and ADAM17 in rat primary cortical neurons treated with interleukin (IL)-1β (to up-regulate P2Y2) or following transfection with P2Y2 [18]. This study also demonstrated a role for phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) in this pathway.…”
Section: Amyloid Precursor Proteinmentioning
confidence: 59%
“…Similarly, UTP induced sAPPα shedding via ADAM10 and ADAM17 in rat primary cortical neurons treated with interleukin (IL)-1β (to up-regulate P2Y2) or following transfection with P2Y2 [18]. This study also demonstrated a role for phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) in this pathway.…”
Section: Amyloid Precursor Proteinmentioning
confidence: 59%
“…Among the G protein-coupled P2YRs, the G q -coupled P2Y 2 R subtype is expressed in neurons and glial cells [13,15,48,[66][67][68]. Our studies using in situ hybridization and reverse transcriptase polymerase chain reaction with rodent brain slices have shown high levels of P2Y 2 R expression in the hippocampus and cerebellum [20], and P2Y 2 R expression can be significantly upregulated in mouse cortical neurons by the proinflammatory cytokine interleukin-1β (IL-1β) [48].…”
Section: P2 Receptors In the Cnsmentioning
confidence: 93%
“…Among cell types that comprise the CNS, mRNAs for P2X1-7 and P2Y 1,2,4,6,11,12,13,14 receptor subtypes have been identified in primary rat astrocytes [4,[41][42][43][44], and their expression patterns can vary with the age of the animal [45,46]. Neurons express mRNAs for P2X3, 5-7 and P2Y 1,2,4,6,12,13 receptors [12,[47][48][49]. Multiple subtypes of P2Rs are expressed in monocytes (P2X1,4,7 and P2Y 1,2,4,6,11,12,13 receptors) [50] and human endothelial cells (P2X4 and P2Y 1,2,4,6,11 receptors) [51].…”
Section: P2 Receptors In the Cnsmentioning
confidence: 99%
See 2 more Smart Citations